Design and development of a graphical user interface for a testing machine with robotic capabilities - Nurul Ashikin Binte Suhaimi (Nanyang Technological University, 2021)
Artificial intelligence is a valuable tool to develop a footwear testing machine for a robotic running foot. Thus, this project aims to improve a user-friendly Graphic User Interface (GUI) system that integrates the overall robotic system and enable cyclic testing to assess the durability and slip resistance of running shoes. The existing mechanism incorporates a realistic robotic foot with ankle and metatarsophalangeal joints that has 6 degrees of freedom (DOF). The artificial foot replicates a human gait using inversion and eversion of forefoot, with a MATLAB Simulink model and DSpace controller to simulate motion. The intuitive GUI implemented will enable users to operate the robotic system in real time with predefined programs within its set parameters and allow ease of accessibility in testing by providing a debugging procedure.